Effective refractive error coverage in adults aged 50 years and older: estimates from population-based surveys in 61 countries. Issue 12 (December 2022) - Bourne, Rupert Richard Alexander; Cicinelli, Maria Vittoria; Sedighi, Tabassom; Tapply, Ian H; McCormick, Ian; Jonas, Jost B; Congdon, Nathan G; Ramke, Jacqueline; Naidoo, Kovin S; Fricke, Timothy R; Burton, Matthew J; Müller, Andreas; et al.
Summary: Background: In 2021, WHO Member States endorsed a global target of a 40-percentage-point increase in effective refractive error coverage (eREC; with a 6/12 visual acuity threshold) by 2030. This study models global and regional estimates of eREC as a baseline for the WHO initiative. Methods: The Vision Loss Expert Group analysed data from 565 448 participants of 169 population-based eye surveys conducted since 2000 to calculate eREC (met need/[met need + undermet need + unmet need]). A binary logistic regression model was used to estimate eREC by Global Burden of Disease (GBD) Study super region among adults aged 50 years and older. Findings: In 2021, distance eREC was 79·1% (95% CI 72·4–85·0) in the high-income super region; 62·1% (54·7–68·8) in north Africa and Middle East; 49·5% (45·0–54·0) in central Europe, eastern Europe, and central Asia; 40·0% (31·7–48·2) in southeast Asia, east Asia, and Oceania; 34·5% (29·4–40·0) in Latin America and the Caribbean; 9·0% (6·5–12·0) in south Asia; and 5·7% (3·1–9·0) in sub-Saharan Africa. eREC was higher in men and reduced with increasing age. Global distance eREC increased from 2000 to 2021 by 19·0%. Global near vision eREC for 2021 was 20·5% (95% CI 17·8–24·4). Interpretation: Over the past 20 years, distance eREC has increased in each super region yet the WHO target will require substantial improvements in quantity and quality of refractive services in particular for near vision impairment. Funding: WHO, Sightsavers, The Fred Hollows Foundation, Fondation Thea, Brien Holden Vision Institute, Lions Clubs International Foundation.